Women in Pauline Theology: A Realistic Appraisal - Pathrapankal, Joseph (Asian Horizons, 2009)
Paul had to suffer a raw deal not only at the hands of those sly feminists but also from those crafty male chauvinists. While the feminists found a scapegoat In Paul to give vent to their pent-up anger towards the male hegemony, those male supremlsts sought the Pauline authentication to legitimize their extreme patriarchal tendencies as If female subordination Is a dlvlnly Instituted, undisputable destiny which weaker sex has to bear meekly. Prof. Joseph Patrapankal In this scholarly as well as Intuitive article, Instead of being apologetic, tries to highlight Paul’s positive contributions and attitude towards women. He also sheds light Into the historical and cultural contexts In which some of those controversial utterences were made. This article Is a sure eyeopener for both the parties who attempt to pull Paul to extremities.